DESIGN THINKING ON WATER MANAGEMENT FOR RESEARCHING PROBLEM SPACES, SOLUTION SPACE AND IMPLEMENTATION SPACE - 1. Dr.Sunil Khilari, 2. Dr.Balasaheb Bhamangol, 3. Prof. Bharati Narute (Journal of the Oriental Institute, ISSN:0030-5324 UGC CARE Group 1, 2024)
We cannot survive without water and if there was no water on earth then there would have been no life. But there are some facts about water that we may unaware of. One indicator of scarcity is attributable to the economic forces that influence different uses of water. The use of water in urban and industrial uses is typically far larger than its use in agriculture. As the population increases market forces will cause a significant reallocation of water resources from the agricultural and environmental areas to the urban areas. This will result in intensifying stress on water based ecosystems and on the food production capacity.Though we have studied and experienced about water, its scientific formula, we even drink it daily as it is a need for survival. Still, there are a lot of things that haven’t been discovered about water. In this paper researcher will going to iidentify Problem Space thatare the well-defined problems from water and agriculture domain. Further to appeal to analyze formalized problem space to formulate corresponding solution space. Then to analyze solution space to formulate implementation space.